Pemberdayaan Kaum Perempuan Melalui Peran Kelompok Wanita Usaha dan Lembaga Keuangan Mikro Di Kelurahan Lalolara Kecamatan Kambu Kota Kendari Sulawesi Tenggara - La Ode Abdul Manan; Imran Imran; Sahyunu Sahyunu; Ridha Taurisma Lajaria Ridha (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Community Service Activities are one of the Tri Dharma of Higher Education that must be implemented. On this occasion, the 2022 service activities were carried out in one of the assisted sub-districts of the Faculty of Economics and Business, University of Southeast Sulawesi, namely the Lalolara Village, which is located in Kambu District, Kendari City, Southeast Sulawesi Province. This time the community service activity raised the theme of Empowering Women Through the Role of Women Business Groups and Microfinance Institutions in Lalolara Village, Kambu District, Kendari City, Southeast Sulawesi. Women in the Lalolara sub-district will be given Bimtek on Financial Management, Business Development Workshops in terms of making Banana Chips and processing plastic waste products (tea glass waste). Weak access to capital in financial institutions such as banks so that women are not maximized and optimal in managing and utilizing alternative business capital, the unstable management of personal finances and the business being run and the need for product innovation resulting from women's business in the Lalolara sub-district.